Symmetric Impact of Carbon Emissions on Poverty in South Africa: New Evidence from ARDL Bounds Test - Khobai, Hlalefang; Stungwa, Sanele; Oliphant, Olebogeng; Maphuto, Oboile; Mbua, Victor Mofema (International Journal of Energy Economics and Policy, 2024)
The purpose of this study is to investigate the relationship between poverty and carbon emissions in South Africa covering the period between 1994 and 2020. The study employed the ARDL bounds test to assess the existence of a long run relationship between the variables. The results evidenced existence of a long run relationship between poverty, carbon emissions, economic growth and renewable energy consumption in South Africa. The results are such that carbon emissions have a positive and a significant effect on poverty in the long run. Therefore, with CO2 emissions having a positive influence on poverty, causes more losses in the socioeconomic system and reduces the ability of the population to cope with poverty. Therefore, it is recommended that the government should promote the growth of the South African carbon market, increase enterprise involvement through acceptable price and quota allocation, and work in tandem with other environmental measures to promote sustainable development. This will help alleviate poverty in South Africa.